Case report: Transition from anti-CD20 therapy to inebilizumab for 14 cases of neuromyelitis optica spectrum disorder - Osborne, Benjamin; Romanow, Gabriela; Hemphill, J. Michael; Zarif, Myassar; DeAngelis, Tracy; Kaplan, Tyler; Oh, Unsong; Pinkhasov, Johnathan; Patterson, Kristina; Levy, Michael (Frontiers in Neurology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disorder of the central nervous system characterized by recurrent, disabling attacks that affect the optic nerve, spinal cord, and brain/brainstem. While rituximab, targeting CD20-positive B-cells, is used as an off-label therapy for NMOSD, some patients continue to exhibit breakthrough attacks and/or adverse reactions. Inebilizumab, a humanized and glycoengineered monoclonal antibody targeting CD19-positive B-cells, has been FDA approved for the treatment of NMOSD in adult patients who are anti-aquaporin-4 (AQP4) antibody positive. Given the limited real-world data on the efficacy and safety of inebilizumab, especially in those transitioning from rituximab, a retrospective chart review was conducted on 14 NMOSD patients from seven centers. Of these, 71.4% (n = 10) experienced a combined 17 attacks during rituximab treatment, attributed to either breakthrough disease (n = 10) or treatment delay (n = 7). The mean duration of rituximab treatment was 38.4 months (3.2 years). Notably, no subsequent attacks were observed during inebilizumab treatment [mean duration of inebilizumab treatment was 19.3 months (1.6 years)], underscoring its potential as an effective treatment for NMOSD. Our data suggest that inebilizumab provides clinical benefit with effective disease control and a favorable safety profile for patients transitioning from rituximab.